2018
DOI: 10.3390/en11092341
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NaCl Concentration on Food-Waste Biochar Structure and Templating Effects

Abstract: Food-waste-derived biochar structures obtained through pyrolysis and with different NaCl concentrations were investigated. Increased NaCl concentration in the samples inhibited cellulose and lignin decomposition, ultimately increasing the biochar yield by 2.7% for 20%-NaCl concentration. NaCl added in solution state exhibited templating effects, with maximum increases in the Brunauer–Emmett–Teller (BET) surface area and pore volume of 1.23 to 3.50 m2∙g−1 and 0.002 to 0.007 cm3∙g−1, respectively, after washing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…We noted that both HPMC E3 and HPMC E5 contain ≤1% sodium chloride [49]. Lee et al observed a sharp diffraction peak at 31.5 • in the X-ray diffractogram of sodium chloride [50]. Therefore, the diffraction peak seen around 31.5-31.7 • in the diffractograms of the Lots 1 and 2 KSDs is attributed to the presence of sodium chloride.…”
Section: Physicochemical Characterization Of Binary Ksdsmentioning
confidence: 97%
“…We noted that both HPMC E3 and HPMC E5 contain ≤1% sodium chloride [49]. Lee et al observed a sharp diffraction peak at 31.5 • in the X-ray diffractogram of sodium chloride [50]. Therefore, the diffraction peak seen around 31.5-31.7 • in the diffractograms of the Lots 1 and 2 KSDs is attributed to the presence of sodium chloride.…”
Section: Physicochemical Characterization Of Binary Ksdsmentioning
confidence: 97%
“…Among the numerous chemical reagents that can be used to create porosity in carbon, sodium chloride (NaCl) was considered as activator due to its low cost, nontoxic, and environmentally friendly. The previous study of biochar produced from food waste has shown that char yield, pore volume, and average pore diameter increases as the impregnated NaCl content increase 9) .…”
Section: Introductionmentioning
confidence: 93%
“…The most significant difference induced by water leaching was salt elimination. KCl and NaCl embedded in the organic material acted as a template, and the pore structure in the material developed after salt dissolution by water leaching [17].…”
Section: Effect Of Pyrolysis Temperature and Modification On Sargassum Biochar's Physicochemical Propertiesmentioning
confidence: 99%